Near real-time monitoring of significant sea wave height through microseism recordings: An application in the Ligurian Sea (Italy). (1st November 2018) - Ferretti, Gabriele; Barani, Simone; Scafidi, Davide; Capello, Marco; Cutroneo, Laura; Vagge, Greta; Besio, Giovanni
Abstract: The monitoring of sea wave parameters, such as the significant wave height, represents a fundamental issue for several economic activities. The use of buoy networks is nowadays a standard approach in sea wave monitoring. However, due to their maintenance costs, both a widespread coverage of monitored areas and the acquisition of continual stream of data appear problematic in any coastal area. In this work, we present an automatic procedure for the near real-time monitoring of the significant sea wave height through microseism recordings. The procedure relies on a set of empirical prediction relations that are calibrated on existing datasets of hindcast sea wave heights, which were computed from wave modeling in the Mediterranean basin. This automatic procedure is developed and tested for monitoring the sea wave height along the Ligurian coast, covering an area of almost 5000 km 2 . On average, our predictions are found to be within a few centimeters from the reference hindcast data, thus showing the overall reliability of the procedure. The accuracy of our procedure has been also confirmed by the good agreement between the predicted significant sea wave heights and the sea wave heights measured at two buoys in the Ligurian Sea, with differences that, on average, are within 20 cm. Compared to conventional monitoring systems based on wave measuring buoys, the procedure proposed in this work allows the minimization of data acquisition interruption due to instrumental breakage, and a widespread, uniform monitoring of sea areas, particularly in the proximity of the shoreline, where structures and infrastructures are more exposed to sea storms. Highlights: Microseismic recording is proved to be a reliable proxy to measure sea wave height. Differences with conventional buoy measurements are, on average, within 20 cm. Microseism-based monitoring procedures allow temporal continuity in data acquisition. Microseism-based procedures allow a widespread, uniform monitoring of sea areas.